Implementasi Prinsip Pembangunan Berkelanjutan dalam Penegakan Hukum Lingkungan Hidup di Kota Padang, Sumatera Barat: Upaya Integrasi antara Kepentingan Ekonomi dan Pelestarian Alam - Adisti Vadila; Aldri Frinaldi; Rembrand Rembrand; Dasman Lanin; Mhd. Ridha (Journal of Innovative and Creativity, 2025)
Environmental law enforcement today faces increasingly complex challenges, particularly in efforts to balance economic development and environmental protection interests. This study aims to examine the application of sustainable development principles in environmental law enforcement in Padang City, West Sumatra, emphasizing the role of local government, law enforcement agencies, and the community in harmoniously integrating economic and ecological aspects. The method applied in this study is qualitative, using a descriptive analysis approach through policy reviews, in-depth interviews, and observations of the implementation of local regulations and law enforcement practices in the field. The findings show that the application of sustainable development principles in Padang City still faces obstacles such as ineffective inter-agency coordination, limited human resources in the environmental sector, and low legal awareness among the community and industry players. Nevertheless, progress has been made through strategic city government policies oriented towards increasing supervision and imposing sanctions for environmental violations. The integration of economic interests with environmental preservation is beginning to be seen through environmentally friendly development policies and efforts to encourage green investment. This study confirms that the success of sustainable development does not only depend on regulations.